Improving the Extraction of Photogenerated Electrons with SnO2 Nanocolloids for Efficient Planar Perovskite Solar Cells. (2nd November 2015) - Rao, Hua‐Shang; Chen, Bai‐Xue; Li, Wen‐Guang; Xu, Yang‐Fan; Chen, Hong‐Yan; Kuang, Dai‐Bin; Su, Cheng‐Yong
Abstract : Great attention to cost‐effective high‐efficiency solar power conversion of trihalide perovskite solar cells (PSCs) has been hovering at high levels in the recent 5 years. Among PSC devices, admittedly, TiO2 is the most widely used electron transport layer (ETL); however, its low mobility which is even less than that of CH3 NH3 PbI3 makes it not an ideal material. In principle, SnO2 with higher electron mobility can be regarded as a positive alternative. Herein, a SnO2 nanocolloid sol with ≈3 nm in size synthesized at 60 °C was spin‐coated onto the fuorine‐doped tin oxide (FTO) glass as the ETL of planar CH3 NH3 PbI3 perovskite solar cells. TiCl4 treatment of SnO2 ‐coated FTO is found to improve crystallization and increase the surface coverage of perovskites, which plays a pivotal role in improving the power conversion efficiency (PCE). In this report, a champion efficiency of 14.69% ( J sc = 21.19 mA cm −2, V oc = 1023 mV, and FF = 0.678) is obtained with a metal mask at one sun illumination (AM 1.5G, 100 mW cm −2 ). Compared to the typical TiO2, the SnO2 ETL efficiently facilitates the separation and transportation of photogenerated electrons/holes from the perovskite absorber, which results in a significant enhancement of photocurrent and PCE. Abstract : SnO2 nanocolloids are synthesized for planar CH3 NH3 PbI3 perovskite solar cells . A champion efficiency of 14.69% is achieved for the SnO2 ‐based solar cell, which is superior to the TiO2 ‐based solar cell (13.38%) due to a higher electron mobility and negative conduction band, facilitating the electron injection, charge separation, and collection, which contribute to the improvement of photovoltaic performance.